Ultrawideband radar measurements analysis and processing - Astanin, L. Y.; Kostylev, A. A. (Aleksandr Aleksandrovich) (Institution of Electrical Engineers, 1997)
This book presents a detailed discussion of mathematical models for radar targets and the statistical processing of scattered signals. The efficiency of the regularising algorithms suggested is illustrated with a description of experimental data processing. Further progress in UWB radar systems is closely associated with the design of fast response (picosecond-range) devices, efficient antennas and analogue-to-digital converters for a frequency of 10 GHz. These devices can considerably improve UWB radar performance.